2022
DOI: 10.15342/ijms.2022.611
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Third Molars in Orthodontics: What about Anterior Dental Crowding? - A Systematic Review

Abstract: Background: Third molar influence on anterior crowding is controversial, However, it is assumed that they play a major role in compromising dental arch space. Aim: To review the literature to clarify the role of third molars in anterior crowding and relapse after orthodontic treatment by means of a systematic review. Material and methods: A systematic search was conducted based on an electronic search of several databases (Pub Med, ScienceDirect, Cochrane Library) covering publications from 2010 to January 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Some orthodontists and oral surgeons recommend extracting third molars to prevent the crowding of teeth upon their eruption [30]. However, recent studies do not present sufficient evidence to advocate the preventive removal of wisdom teeth to obtain occlusal stability [31,32]. The study of Dosumu et al showed poor knowledge of the consequences of missing teeth among patients with partial edentulism [28].…”
Section: Missing Teethmentioning
confidence: 99%
See 1 more Smart Citation
“…Some orthodontists and oral surgeons recommend extracting third molars to prevent the crowding of teeth upon their eruption [30]. However, recent studies do not present sufficient evidence to advocate the preventive removal of wisdom teeth to obtain occlusal stability [31,32]. The study of Dosumu et al showed poor knowledge of the consequences of missing teeth among patients with partial edentulism [28].…”
Section: Missing Teethmentioning
confidence: 99%
“…[42] Implants were often inserted around tooth FDI 26/UNS 14 (6 times). In the study group, implants were not placed in the place of teeth FDI 18,17,28,38,37,[34][35][36][37][38][39][40][41][42][43][44]47,48/UNS 1,2,16,17,18,[21][22][23][24][25][26][27][28]31,32. According to a report concerning trends in dental implants in the US in 1999-2016, most were placed in posterior sites, almost equally in the maxilla and mandible [43]. The anterior maxillary region, being an aesthetic zone, requires special attention in the treatment plan to eliminate the risk of positioning errors, considering gingival phenotype, the width of the edentulous space, and bone anatomy at the alveolar crest [44].…”
Section: Restoring Missing Teeth With Dental Implants and Bridgesmentioning
confidence: 99%
“…Even though a recently published systematic review reported that only 6 studies were selected in the quantitative synthesis and none of these studies used CBCT for evaluation of such 3D problem [17]. Thus, there is a great inconsistency in studies regarding to the relationship of IM3M and other dental arch parameters like anterior crowding, at the same time using more reliable diagnostic tool like 3D CBCT to add well designed study with comprehensive three-dimensional measurements to the existing literature.…”
Section: Introductionmentioning
confidence: 99%